Jews in contemporary visual entertainment : raced, sexed, and erased - Siegel, Carol 1952- (Indiana University Press, 2022)
What are the consequences of how Jews are depicted in movies and television series? Drawing on a host of movies and television series from the 1970s to present day, Jews in Contemporary Visual Entertainment explores how the media sexualize and racialize American Jews. Race and sexuality frequently intersect in the depiction of Jewish characters in such shows as The Marvelous Mrs. Maisel, UnREAL, The Expanse, and Breaking Bad, and in films such as Hester Street, Once Upon a Time in America, Casino, Radio Days, Inglourious Basterds, and Barton Fink. When they do, American sexual norms are invariably challenged or outright broken by these anti-Semitic representations of Jewishness. Insightful and provocative, Jews in Contemporary Visual Entertainment disturbingly reveals the far-reaching influence of popular visual media in shaping how American Jews are perceived today.